Ligand-based discovery of novel trypanosomicidal drug-like compounds: In silico identiﬁcation and experimental support - Castillo Garit, Juan Alberto; Vega, María Celeste; Rolón, Miriam; Marrero Ponce, Yovani; Gómez Barrio, Alicia; Escario, José Antonio; Álvarez Bello, Alfredo; Montero Torres, Alina; Torrens, Francisco; Pérez Giménez, Facundo; Arán, Vicente J.; Abad, Concepción (My University, 2011)
Two-dimensional bond-based linear indices and linear discriminant analysis are used in this report to perform a quantitative structureeactivity relationship study to identify new trypanosomicidal compounds. A database with 143 anti-trypanosomal and 297 compounds having other clinical uses, are utilized to develop the theoretical models. The best discriminant models computed using bond-based linear indices provides accuracies greater than 90 for both training and test sets. Our models identify as anti-trypanosomals ﬁve out of nine compounds of a set of already-synthesized substances. The in vitro anti-trypanosomal activity of this set against epimastigote forms of Trypanosoma cruzi is assayed. Both models show a perfect agreement between theoretical predictions and experimental results. The compounds identiﬁed as active ones show more than 98% of anti-epimastigote elimination (AE) at a concentration of 100 mg/mL. Besides, three compounds show more than 70% of AE at a concentration of 10 mg/mL. Finally, compounds with the best “activity against epimastigote forms/unspeciﬁc cytotoxicity” ratio are evaluated using an amastigote susceptibility assay. It should be noticed that, compound Va7-71 exhibit a 100% of intracellular amastigote elimination and shows similar activity when compared to a standard trypanosomicidal as nifurtimox. Finally, we can emphasize that, the present algorithm constitutes a step forward in the search for efﬁcient ways of discovering new anti-trypanosomal compounds
Keywords: Bond-based linear indices; Trypanosoma cruzi; Trypanosomicidal; Anti-epimastigote elimination; Amastigote susceptibility assay; Trypanosoma cruzi